2016
DOI: 10.1007/s13365-016-0499-3
|View full text |Cite
|
Sign up to set email alerts
|

Immortalization of primary microglia: a new platform to study HIV regulation in the central nervous system

Abstract: The major reservoirs for HIV in the CNS are in the microglia, perivascular macrophages, and to a lesser extent, astrocytes. To study the molecular events controlling HIV expression in the microglia, we developed a reliable and robust method to immortalize microglial cells from primary glia from fresh CNS tissues and commercially available frozen glial cells. Primary human cells, including cells obtained from adult brain tissue, were transformed with lentiviral vectors expressing SV40 T antigen or a combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
234
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(242 citation statements)
references
References 98 publications
8
234
0
Order By: Relevance
“…The human microglial cell line, hμglia, was a kind gift from Dr. Jonathan Karn (Case Western Reserve University). These cells were derived from primary human cells transformed with lentiviral vectors expressing SV40 T antigen and hTERT, and have been classified as microglia due to their microglia-like morphology, migratory and phagocytic activity, presence of the microglial cell surface markers CD11b, TGFβR, and P2RY12, and characteristic microglial RNA expression profile [16]. This cell line was maintained in Dulbecco’s Modified Eagle Medium supplemented with 5% FBS and penicillin/streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…The human microglial cell line, hμglia, was a kind gift from Dr. Jonathan Karn (Case Western Reserve University). These cells were derived from primary human cells transformed with lentiviral vectors expressing SV40 T antigen and hTERT, and have been classified as microglia due to their microglia-like morphology, migratory and phagocytic activity, presence of the microglial cell surface markers CD11b, TGFβR, and P2RY12, and characteristic microglial RNA expression profile [16]. This cell line was maintained in Dulbecco’s Modified Eagle Medium supplemented with 5% FBS and penicillin/streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…In this respect, human microglial cell lines allow to overcome this problem and can be considered a valuable experimental model. Several cell lines have been generated in different laboratories [17,18], including more recent lines derived from adult brain tissue [19]. All these cell lines were developed through SV40 immortalization of human primary microglial cells, whereas a fraction of SV40-immortalized adult microglial cells were further engineered to express the human telomerase reverse transcriptase (hTERT) and reduce the proliferation rate [19].…”
Section: Introductionmentioning
confidence: 99%
“…Several cell lines have been generated in different laboratories [17,18], including more recent lines derived from adult brain tissue [19]. All these cell lines were developed through SV40 immortalization of human primary microglial cells, whereas a fraction of SV40-immortalized adult microglial cells were further engineered to express the human telomerase reverse transcriptase (hTERT) and reduce the proliferation rate [19]. To the best of our knowledge, two cell lines are commercially available, the human microglial clone 3 cell line, HMC3 [17,[20][21][22] and the "Immortalized Human Microglia -SV40", developed and distributed by Applied Biological Materials (Vancouver, Canada) [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…LPS: lipopolysaccharide; TLR4: tolllike receptor 4; RT-PCR: real-time polymerase chain reaction; US: unstimulated; SDS-PAGE: sodium dodecyl sulfate polyacrylamide gel electrophoresis Interestingly, a recent publication [25] suggested that CHME-5 cells are of rat origin, not human. In the study, they performed genotyping by macrosatellite a na lys i s, a n d i nve st i g ate d t h e CYCT1 g e n e expression in CHME-5 cells using both human and rat primers, and showed rat CYCT1 gene expression, but not the human counterpart in these cells [25] . The CHME-5 cell line currently being used in numerous labs is apparently of non-human origin, but to our knowledge this has yet to be independently verified.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, during our review of the literature we identified an article characterizing primary human microglia in which data revealed large inconsistencies in microglial and inflammatory genes between primary human microglia and human microglial cell lines, including CHME-5 cells [26] . Knowing what we do now about the non-human origin of CHME-5 cells from Garcia-Mesa et al [25] 2017, the inability to detect gene expression might have been due to the use of human primers. Taking this into consideration, we characterized TLR4 neuroinflammatory signaling in CHME-5 cells, as a rat cell line, validated that these cells are not of human origin, and demonstrated that CHME-5 cells remain a viable tool to study microglial-like inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%